Perilaku Kekerasan terhadap Anak dalam Perspektif Hukum Keluarga Islam: Analisis Faktor Penyebab, Dampak Psikologis, dan Upaya Penanggulangan - Suryantoro, Dwi Dasa (UAS PRESS, 2025)
This study aims to analyze violent behavior against children from the perspective of Islamic family law by examining the causative factors, psychological impacts, and efforts to overcome them through positive legal instruments and Islamic values. The research method used is a qualitative approach with literature study techniques, where the author examines various written sources, such as books, scientific articles, and legal regulations related to child protection. The data obtained were analyzed descriptive-analytically with a normative juridical approach to uncover the relationship between the factors that cause violence against children, the psychological impact it causes, and the relevant coping mechanisms. The results of the study show that violence against children is caused by complex individual, family and social factors, and negatively impacts children's physical, emotional, and psychological development. In terms of positive law, regulations in Indonesia have provided quite comprehensive protection, although their implementation still faces cultural barriers and weak law enforcement. Meanwhile, in Islamic family law, children are seen as the mandate of Allah SWT that must be cared for and treated with affection, so that violence in parenting cannot be justified. The recommendations of this study emphasize the importance of synergy between positive legal instruments and Islamic values in building a complete child protection system, by involving families, communities, and the state collaboratively.